Clustering Data On Underage Marriage Using The Clustering Method - Sonadi Perangin Angin; Rusmin Saragih; Marto Sihombing (Yayasan Kita Menulis, 2023)
In Law no. 1 of 1974, article 7 paragraph (1) states that marriage is only permitted if the man has reached the age of 19 and the woman has reached the age of 16. Nationally, early marriage to the age of under 16 is 26.95%. In fact, based on the findings of Bappenas in 2008, it was stated that 34.5% of the 2,049,000 marriages in 2008 until now were child marriages which were increasing rapidly (Rifiani, 2011: 126). The influence of foreign culture is also one of the causes of the large number of underage marriages, foreign cultures which are very famous for freedom of dating, are the views of today's youth to have relations outside of legal marriage. Not only culture, information technology in the 4.0 era has greatly influenced the occurrence of underage marriages, adult video sites that are easily accessible via the internet. For this reason, the K-means clustering method is used as the right solution for the problem of underage marriage data by grouping the data based on age, gender, and occupation to get definite data, so that data grouping using the applicationmatlab andrapid miner can produce output from data mining that can be used in making decisions in the future Keywords: Underage marriage, clustering, matlab